An exploratory study on the prevalence of workplace violence: the case of Algerian hospitals - Heddar, Yamina; Djebabra, Mébarek; Saadi, Saadia (Employee Relations, 2022)
Purpose Workplace violence is a universal phenomenon that is constantly increasing. In this regard, this study aims to investigate the prevalence of violence committed against Algerian health professionals. Design/methodology/approach A cross-sectional survey, based on an anonymous, self-administered questionnaire, was conducted in healthcare settings of eastern Algeria (where 144 respondents participated in this study). Besides, socio-demographic characteristics and data related to violence, including its prevalence, different forms, perpetrators, reporting and the way it is handled, were analyzed using descriptive and inferential statistics. Findings Half of the respondents were victims of violence. More specifically, 90.1% of them were verbally abused. Compared to physical violence, verbal violence was significantly perpetrated against women and young health professionals (p < 0.05). However, nurses and those with less than or equal to five years of work experience were the most vulnerable to both types of violence (p < 0.05). Moreover, the main perpetrators were the patients' relatives (70%) followed by the patients themselves (51.4%). In terms of risk treatment, aggressors were verbally warned (60%). For violence reporting, 31% of the respondents observe such a fact as not being important. Finally, 65.7% of the participants reported that their employers had provided them with security measures (guards). Originality/value This is the first study conducted in Algeria that examines the prevalence of violence and its relationship with socio-demographic characteristics. Authorities must react effectively to solve this problem by implementing preventive and anticipatory strategies.